2005
DOI: 10.1177/00238309050480030401
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Phonological Quantity based on Durational Cues by Native Speakers, Second-language Users and Nonspeakers of Finnish

Abstract: Some languages, such as Finnish, use speech-sound duration as the primary cue for a phonological quantity distinction. For second-language (L2) learners, quantity is often difficult to master if speech-sound duration plays a less important role in the phonology of their native language (L1). By comparing the categorization performance of native speakers of Finnish, Russian L2 users of Finnish, and non-Finnish-speaking Russians, the present study aimed to determine whether the L2 users, whose native language do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
8
31
0
Order By: Relevance
“…In this case, the present data must be interpreted as Russian listeners' assimilating ͓i͔ to a longer ͑stressed͒ category, and ͓(͔ to a shorter one ͑per-haps prestressed͒, in a pattern of two-category assimilation ͑Best, 1995͒. A similar explanation has been advanced by Ylinen et al ͑2005͒ to explain monolingual Russian listeners' treatment of the Finnish vowel length contrast. This interpretation is also consistent with the observed lack of a significant correlation found between the results of experiments 1 and 2.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this case, the present data must be interpreted as Russian listeners' assimilating ͓i͔ to a longer ͑stressed͒ category, and ͓(͔ to a shorter one ͑per-haps prestressed͒, in a pattern of two-category assimilation ͑Best, 1995͒. A similar explanation has been advanced by Ylinen et al ͑2005͒ to explain monolingual Russian listeners' treatment of the Finnish vowel length contrast. This interpretation is also consistent with the observed lack of a significant correlation found between the results of experiments 1 and 2.…”
Section: Discussionsupporting
confidence: 61%
“…The structure of the practice session was identical to the actual experiment but responses were not recorded. proficiency and the relative weighting given to spectrum versus duration ͑Piske et al, 2001;McAllister et al, 2002;Ylinen et al, 2005͒. Factors ͑predictor variables͒ were ͑see Table I͒: ͑1͒ age of participant, ͑2͒ age of arrival ͑AOA͒ in the USA, ͑3͒ length of residency ͑LOR͒ in the USA, ͑4͒ age of starting English as a foreign language ͑EFL͒ education in the home country, ͑5͒ period of EFL in the home country, ͑6͒ period of English as a second language ͑ESL͒ study in the USA after arrival, ͑7͒ age of starting formal education in the USA, ͑8͒ period of formal education in the USA, ͑9͒ self-estimated degree of motivation in using ESL, ͑10͒ self-estimated degree of imitation abilities, ͑11͒ self-estimated degree of using ESL at home, ͑12͒ self-estimated degree of using ESL in a social environment, and ͑13͒ self-estimated degree of using ESL at work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMN effects corresponding to the category-boundary (Liberman et al, 1957) as well as to the perceptual magnet effect (Kuhl, 1991) have been observed. With many studies using cross-linguistic controls, across-category contrasts yielded higher-amplitude and/or earlier MMN responses than withincategory ones (Dehaene-Lambertz, 1997;Näätänen et al, 1997;Phillips et al, 2000;Winkler et al, 1999;Ylinen et al, 2005). Further, near-prototype contrasts elicited lower-amplitude MMNs than within-category contrasts between less typical pairs having equal acoustic separation (Aaltonen et al, 1997).…”
Section: Object Representations and Category Effectsmentioning
confidence: 97%
“…Previous research has found the Finnish quantity feature to be difficult to perceive, produce and spell for both literate L2 Finnish learners (see Nenonen et al, 2003;Ullakonoja, Kuronen, Hurme, & Dufva, 2014;Ylinen, Shestakova, Alku, & Huotilainen, 2005) as well as pre-literate and low-literate L2 Finnish learners (Heikkinen, 2009;Malessa, 2016). Heikkinen (2009, p. 49) found in her study that LESLLA learners struggled with the quantity distinction of both double vowels and geminates and revealed that most quantity errors concerned the distinction between /k/ -/kk/ and/v/ -/vv/.…”
Section: Computer-assisted Language Learning In Literacy Development mentioning
confidence: 98%